2011
DOI: 10.1007/s12029-011-9283-z
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Submucosal Dissection Combined with the Placement of Biodegradable Stents for Recurrent Esophageal Cancer After Chemoradiotherapy

Abstract: We report a case of a patient with esophageal squamous cell carcinoma who presented with obstruction of the esophagus. On endoscopy, a central ulcerating lesion was found spreading to the anterior wall of the middle esophagus. Four courses of chemoradiation therapy successfully produced a complete response for 3 years. A recurrence occurred which consisted of a morphologically flat lesion that occupied the entire circumference of the esophagus. Endoscopic submucosal dissection removed all lesions en bloc. To p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…Therefore, it is plausible that our study found a higher incidence of total esophageal stricture due to the high percentage of patients presenting with wide esophageal lesions. Overall, the results of this retrospective study indicate a number of independent risk factors for the development of esophageal stenosis following ESD, which are in line with findings of other studies [13][14][15][16][17][18][19][20][21]. Mizuta et al [13] highlighted that the primary contributor to esophageal stenosis following ESD was the area of periesophageal mucosal defect exceeding 71%.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, it is plausible that our study found a higher incidence of total esophageal stricture due to the high percentage of patients presenting with wide esophageal lesions. Overall, the results of this retrospective study indicate a number of independent risk factors for the development of esophageal stenosis following ESD, which are in line with findings of other studies [13][14][15][16][17][18][19][20][21]. Mizuta et al [13] highlighted that the primary contributor to esophageal stenosis following ESD was the area of periesophageal mucosal defect exceeding 71%.…”
Section: Discussionsupporting
confidence: 90%
“…Despite concerns about the stability of an oesophageal stent in the nonstrictured oesophagus, the potential tissue ingrowth at the ends of the stent leading to stent‐induced strictures, and the circumferential mucosal lesion left in the oesophagus after stent removal that is itself prone to stricturing, prophylactic stent placement has been assessed in patients. A case report mentioned the absence of efficacy of biodegradable stents for stricture prevention . Holt et al .…”
Section: Resultsmentioning
confidence: 96%
“…A case report mentioned the absence of efficacy of biodegradable stents for stricture prevention. 110 Holt et al assessed in 12 patients fully covered metal stents, placed 10 days after a circumferential EMR for Barrett's neoplasia: in four patients, stents had to be removed for pain or dysphagia, and 57.5% of the patients ultimately developed strictures. 111 Another team, in the same clinical setting, reported a 28% stricture rate after oesophageal stent removal or migration.…”
Section: Mechanical Approachmentioning
confidence: 99%
“…There are concerns about the technical difficulty of ESD and possible complications from ESD after CRT. Although data on the outcomes of esophageal ESD after CRT are limited, several Japanese authors have reported favorable outcomes for esophageal ESD after CRT [ 3 , 8 - 10 ]. In addition, our two patients showed favorable outcomes without complications.…”
Section: Discussionmentioning
confidence: 99%